Risk Assessment of Operation and Maintenance of Wind Turbines in the Arctic [poster] - Mustafa, Albara Mohamad Yazid Faisal; Barabadi, Abbas (UIT The Arctic University of Norway, 2019)
Published: https://www.arcticfrontiers.com/wp-content/uploads/downloads/2019/Arctic%20Frontiers%20Science/Poster%20presentations/4232675_Albara.pdf